2021
DOI: 10.1021/acs.jafc.1c05364
|View full text |Cite
|
Sign up to set email alerts
|

Taking Advantage of the Renewable Forest Bioresource Turpentine to Prepare α,β-Unsaturated Compounds as Highly Efficient Fungicidal Candidates

Abstract: In a continuous study on the high-value-added exploration of a renewable forest bioresource turpentine in modern organic agriculture, two series of α-pinene derivatives containing amide and α,β-unsaturated ketone pharmacophores were prepared. Through an in-depth fungicidal activity study, the title compounds presented excellent inhibitory activity against common crop fungi, especially Sclerotinia sclerotiorum, and the notable EC50 values of α,β-unsaturated compounds 3u (funan containing) and 3v (thiophene cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…When the same substituent groups were introduced into the benzene ring of the derivatives, the number of substituent groups had improved the antifungal activity against T. versicolor [ 38 ]. It was found that derivatives monosubstituted with fluorine exerted stronger antifungal activity than those polysubstituted with fluorine ( 4b–4d > 4l–4n ; 5b–5d > 5m ) corroborating of prior research [ 39 ]. The analysis of the effect of substituent position in the benzene ring on antifungal activity against T. versicolor showed that derivatives with a substituent group at the para-position generally gave better antifungal activity ( 4d > 4b , 4c ; 4k > 4i , 4j ; 5k > 5j , etc.).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…When the same substituent groups were introduced into the benzene ring of the derivatives, the number of substituent groups had improved the antifungal activity against T. versicolor [ 38 ]. It was found that derivatives monosubstituted with fluorine exerted stronger antifungal activity than those polysubstituted with fluorine ( 4b–4d > 4l–4n ; 5b–5d > 5m ) corroborating of prior research [ 39 ]. The analysis of the effect of substituent position in the benzene ring on antifungal activity against T. versicolor showed that derivatives with a substituent group at the para-position generally gave better antifungal activity ( 4d > 4b , 4c ; 4k > 4i , 4j ; 5k > 5j , etc.).…”
Section: Resultssupporting
confidence: 86%
“…Based on the SAR and QSAR of the present study, although fluorine atoms improved the antifungal activity of the camphor derivatives, greater numbers of fluorine atoms did not necessarily increase the antifungal activity of the camphor derivatives. Interestingly, a previous study drew similar conclusions [ 39 ].…”
Section: Resultssupporting
confidence: 73%
“…Nopinic acid (2) was prepared using our previously reported method. 13 Compound 2 (2 mmol) was dissolved in 30 mL of CH 2 Cl 2 , and 3 mL of SOCl 2 was added to the mixture and refluxed for 4 h. After completion, excess CH 2 Cl 2 and SOCl 2 were removed to obtain compound 3. Compound 5 (2 mmol) and N,N′-dicyclohexylcarbodiimide (2 mmol) were dissolved in 8 mL of CH 2 Cl 2 , to which compound 3 (2 mmol) was added in an ice bath.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…13,14 Pinonic acid is a pinene-derived lead compound that has a quaternary ring and two chiral centers through functional group expansion and has been reported to possess potent antifungal activity (Figure 1). 13 Some active fragments have been combined in an ongoing effort to develop novel pesticides with optimal activity and diverse action modes. Oxime esters have been used in various fungicides because they are considered a remarkable and simple motif for modern pesticide invention.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Effect of Compound 12p on the Mycelial Morphology, Organelles, and Fruit Body Production of V. mali. 33,34 The mycelia were inoculated with or without compound 12p at a concentration of 3.2 μg/mL at 25 °C. The mycelial morphology and the fungal organelles at the top of each treated colony were observed under an SEM (5 kV, 500−3000×) and a TEM (80 kV, 8000−50 000×), respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%